SOCIAL FACTORS OF CREATIVITY OF EMPLOYEES: EXAMINING THE RELATIONSHIP BETWEEN ORGANIZATIONAL MOTIVATION, MANAGEMENT TRAINING, AND AVAILABILITY OF RESOURCES. A CASE STUDY OF WAPDA, FESCO, FAISALABAD - Manahil Jabbar, Babak Mahmood, Muhammad Furqan Ashraf, Paris Zaka, Zaid Mehmood (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This research was based on social factors of creativity of employees and examined the working environment through the relationship between creativity, organizational motivation, management training and availability of resources. Quantitative research method was used to conduct the study through field visits. Middle managers of WAPDA, FESCO were population of study. Simple random sampling was used to select a sample of 120 middle managers. Data was collected through primary source through field visits. A well established questionnaire was used to collect primary information from middle managers. The collected data was analysed by using SPSS 20. Finding of the study revealed that various social factors are responsible for improving creativity skill of middle managers i.e. organizational motivation, management training and available resources, strict control and encouragement were found influential social factors to boost up the creativity skill of middle managers that canhelp in improving ultimate productivity of employee and also achieve organizational goals within stipulated domain. It was recommended that training of employees must be conducted on consistent basis. Availability of resources create potential work for organizations, therefore, its timely up gradation and availability must be ensured.